GROWTH AND RESULTS OF ThePanicum maximum GRASS GIVEN THE VARIOUS DOSES OF N AND P FERTILIZER ON DIFFERENT SOIL TYPES - i M. P., Aryana; Roni, N. G. K.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
The research aims to determine the  Panicum maximum  growth and yield of grass planted in three different soil types namely the Latosol, Regosol and Mediterranean soils, with different applications of fospat and nitrogen fertilizers. The research was conducted from May to July, in Sading Village, Kec. The Badung. The draft used in this study is a complete random draft (RAL) pattern split-plot. The first factor is the type of soil and the second factor is the dose of fertilizer, with three treatments and four times repeated, three treatment of fertilizer treatment D1 (fertilizer dose 100 kg N/ha), and D2 (fertilizer dose 50 kg N/ha + 50 kg P/ha, and D3 (fertilizer 100 kg P/ha), repeated 4 times so there are 36 research pots. The observed variables are growth, yield and plant characteristics. The results showed the growth, results and characteristics of the dose of the fertilizer showed differently not real (P>0.05) on all the variables but the three types of soil showed a distinct real (P<0.05), on all variables except crop height, number of leaves, Number of tillers and dry weight ratio of leaves with stem. Based on the results of the studies can be concluded that the growth, results and the best of  Panicum maximum  grass characterized at the treatment of fertilizer dose 50 kg N/ha + 50 kg P/ha. The growth, results, and characteristics of the finest of  Panicum maximum  grass are found in Mediterranean soil type. The interaction between fertilizer and soil types occurs on the number of leaves, number of saplings, and the area of  Panicum maximum  grass leaves.   Keywords: Panicum maximum grass, Nitrogen Fertilizer, Fospat fertilizer, Soil type